Microfoundations of dynamics capabilities: a lab experiment on cognitive processing and routine adaptation - Alves, Marlon Fernandes Rodrigues (2019)
Dynamic capabilities have been recognized as the key explanation of firm heterogeneity and a potential source of sustainable competitive advantage. However, a few empirical previous studies connected dynamic capabilities to individual action, nor do they take the opportunity to investigate cognitive processes underlying capability deployment. A central issue here is the emphasis only on the effects and the antecedents of dynamic capabilities, so existing research does not shed light on what are the lower-level elements that constitute a capability-its microfoundations. To fill this gap, we conducted a lab experiment with executives where we examine the effect of priming intuitive and reflective cognitive processing on routine adaptation after an exogenous shock. We provide evidence that teams under the intuition condition cope better with environmental changes than the ones under the reflection condition. We also found evidence that environments with more feedback-learning opportunities (i.e. more stable) facilitate routine adaptation. Further, we show that the payoffs for intuition rather than reflection are higher in environments with less feedback opportunities. These findings redirect the current understanding of intuitive thinking in organizational change. In sum, our study contributes to providing a micro-level account of firms\' dynamic capabilities.